The Impact of Modern Technologies on Human Rights - Bernadetta STACHURA-TERLECKA (Communications of International Proceedings, 2024)
This article discusses the impact of modern technologies on human rights. Existing legislative solutions related to new technologies will be presented, along with an analysis aimed at indicating how modern technology and its individual elements affect human rights. Contemporary humans live in two worlds (digital and real), making it crucial to understand how modern technology impacts human rights. This study was conducted in the form of an analysis of contemporary legal acts passed both in the European Union and in Poland, and an analysis of the individual influences associated with various aspects and tools of modern technology.
Keywords: Modern Technologies; Human Right; SI; IoT